SUSTAINABLE ENERGY FOR RADAR SYSTEMS IN INDONESIA'S OUTERMOST ISLANDS: A COOPERATIVE GAME THEORY ANALYSIS - Rakhmad Susilo; Mukhlis; Chairul Imron; Okol Sri Suharyo; Riko Fendiawan (Indonesian Naval Technology College STTAL, 2024)
Indonesia's vast territorial waters, essential for natural wealth and strategic trade routes, face significant security challenges, including smuggling, illegal fishing, marine pollution, and maritime terrorism. To address these threats, Indonesia has implemented the Integrated Maritime Surveillance System (IMSS), primarily powered by diesel generators and, in some cases, supplemented by solar cells. This study explores the potential of transitioning IMSS to sustainable energy sources, specifically solar cells, to enhance environmental sustainability and operational independence. Utilizing cooperative game theory, we analyze the compromise values of using solar cells, diesel generators, and PLN (state electricity) to determine the optimal energy mix that balances costefficiency and renewable energy utilization. Through cooperative game theory, we evaluate the total costs andnet present values (NPV) of each energy source under different usage scenarios (100%, 75%, 50%, and 25%). The NPV method is applied to assess the profitability and cost-effectiveness of each energy source over a 10-year period, discounting future cash flows to present value to account for the time value of money. This analysis shows that while solar cells require high initial investment, they offer significant long-term operational cost savings and environmental benefits. Conversely, diesel generators, despite lower initial costs, incur high operational and maintenance expenses. PLN electricity, though reliable in certain areas, faces limitations in remote regions. By determining the payoff matrix and eliminating dominant strategies, we identify the optimal compromise strategy that maximizes the use of renewable energy while minimizing costs. This approach not only supports Indonesia's green economy initiatives but also ensures reliable and efficient maritime surveillance. The findings advocate for a strategic shift towards greater reliance on solar energy for IMSS, promoting environmental sustainability and enhancing the system's overall effectiveness in securing Indonesia's maritime domain. This study contributes to the broader discourse on sustainable energy transitions in critical infrastructure and highlights the applicability of cooperative game theory in resource management.